Statistical study on the improvement of corner kicks in junior football players through specific means - Tatarcan Cătălin-Andrei (Editura Univeristatii "Stefan cel Mare" din Suceava, 2022)
The article aims to improve the technical execution of hitting and passing the ball from the corner of the field with enough precision and force to reach a teammate in the opposing box. The study was carried out in the Luceafărul Bucovina Club, where players from the midfielder position, forwards and defenders were used. The experimental group is engaged in the Under 15 county football championship, while the control group does not participate in any official competition. The experiment was carried out over a period of 3 weeks, and 3 specific exercises were applied to improve the execution of corner kicks.